Physical and chemical changes in lignite during mechanical and thermal dewatering process and associated changes in the organic compounds in the wastewater. Issue 4 (3rd April 2022) - He, Qiongqiong; Yeasmin, Hasina; Hoadley, Andrew; Qi, Ying
ABSTRACT: Mechanical thermal expression (MTE) was used for dewatering two lignites, Loy Yang (LY) from Australia and Shengli (SL) from China. The dewatering process was carried out with temperatures ranging from 24°C to 240°C. It was found that the moisture content of the MTE products decreased linearly with increasing temperature, and the residual moisture content was a function of compressibility. The MTE process was more effective for the low-rank LY lignite. The characterization of the lignite includes moisture content, C/H ratio, pore volume distribution from mercury intrusion porosimetry and, coal–water interaction from low-field nuclear magnetic resonance (LFNMR). Coal–water interaction only changed slightly with mechanical compression alone. Combined with heat mechanical effect found to compress the residual moisture into smaller pores. The coal–water interaction is stronger in the smaller pores, which makes dewatering progressively more difficult. The chemical characteristics were studied by solid-state 13 C NMR, where no significant changes were apparent. Total organic carbon (TOC) analysis showed higher content of organics in the LY wastewater than in the SL wastewater. The chemical composition of the wastewater was analyzed by gas chromatography–mass spectrometry (GC-MS) and it was found that the majority of the compounds from LY and SL detected were acids, accounting for more than 50% of the organic compounds, followed by aromatic hydrocarbons, accounting for 27% in LY and 38% in SL wastewater. Lower levels of alkenes, alcohols, esters, and aliphatic hydrocarbons were also found in the wastewater.